DIALEKTIKA HUKUM DAN TEKNOLOGI DALAM MENGHADAPI KONFRONTASI ERA TRANSFORMASI INDUSTRI 5.0 TERHADAP LOCAL WISDOM - Aullia Vivi Yulianingrum (Jurnal Hukum Lex Generalis, 2024)
The transition to Society 5.0 signifies the deep integration of technology into everyday life driven by innovations such as artificial intelligence and the Internet of Things (IoT). This paper explores the dialectical relationship between law and technology in the context of Society 5.0 in facing the confrontation arising from the transformation towards the industrial era 5.0 with a focus on its impact on local wisdom or local wisdom. In the era of industry 5.0, the integration between humans and machines brings fundamental changes to various sectors of life. This change has an impact on the preservation of local wisdom which clashes with fast-paced technological advances. This study examines how law can play a role in regulating and controlling technological developments, whether technology can support or worsen local wisdom. Using a normative juridical methodology with a conceptual approach, this study reveals an imbalance in the development of increasingly advanced technology where legal adaptation is slow in protecting local wisdom. Therefore, it is necessary to understand the interaction of law and technology in the context of 5.0 for policymakers, legal practitioners and parties involved in the preservation of local culture regarding how important the synergy between law and technology is in facing challenges and opportunities in the industrial era 5.0. In addition, this research can be used as literature on law and technology and support the sustainability of local wisdom in the digital era. The study of dialectics between law, technology and local wisdom in the context of industrial transformation is still very limited and new perspectives related to the role of law in protecting local wisdom with the development of technological advancements.